Responsibility to protect and the external security policy of the European Union - Коваль, Дмитро Олександрович; Коваль, Дмитрий Александрович; Koval, Dmytro O. (My University, 2014)
This paper presents the overview of the Responsibility to Protect (R2P) doctrine  implementation  to  the  European  Union  Security  and  Defense  policy.  In  this context, the references on the notion of R2P in the EU documents are  traced. The article defines the main barriers for the effective and progressive  implementation of the mentioned doctrine. Special attention is paid to the  EU participation in the establishment of the internationalized criminal and  human rights tribunals as a form of R2P implementation.
Koval D. Responsibility to protect and the external security policy of the European Union / D. Koval // Evropsky politicky a pravni diskurz = European political and law discourse. - 2014. - Vol. 1. - Iss.5. - P. 15-26.
Keywords: Responsibility to Protect (R2P); European Union; European Union Security; European Union Security and Defence policy; human rights; international law; обов’язок захищати; Європейський Союз; права людини; міжнародне право; обязанность защищать; Европейский Союз; Європейська політика безпеки та оборони; Европейская политика безопасности и обороны; права человека; международное право